Antibacterial, Cytotoxic Studies and Characterization of Some Newly Synthesized Symmetrical N3,N3′-Bis(disubstituted)isophthalyl-bis(thioureas) and Their Cu(II) and Ni(II) Complexes - Muhammad Jamil; Muhammad Zubair; Muhammad Asim Farid; Umer Rashid; Nasir Rasool; Saiful Islam (Journal of Chemistry)
A series of some novel N3,N3′-bis(disubstituted)isophthalyl-bis(thioureas) compounds with general formula [C6H4· {CONHCSNHR}2], where R = 2-ClC6H4S (L1), 3,5-(Cl)2C6H3 (L2), 2,4-(Cl)2C6H3 (L3), 2,5-(Cl)2C6H3 (L4), and 2-NH2C6H4 (L5), and their Cu(II) and Ni(II) complexes (C1–C10) have been synthesized. These compounds (L1–L5) and their metal(II) complexes (C1–C10) have been characterized by elemental analysis, infrared spectroscopy, 1H NMR and 13C NMR spectroscopy, magnetic moments, and electronic spectral measurements. The ligands are coordinated to metal atom in a bidentate pattern producing a neutral complex of the type [ML]2. These compounds (L1–L5) and their metal(II) complexes (C1–C10) were also screened for their antibacterial and cytotoxic activities.